Exercise Consideration for People with Obesity Amidst Covid-19 Pandemic: a Scoping Review - Azrania Fatima; Syifa Eka Rahmawati; Dhiyaa Ulhaq Amatullah; Hartiah Haroen (Universitas Padjadjaran, 2022)
Introduction: The current coronavirus disease 2019 (COVID-19) pandemic has been limiting people’s activities outside the home in order to reduce the spread of the virus. This limitation causes a decrease in people's physical activity patterns. Physical activity is important for people with obesity to avoid further increase in body weight or even to help to reduce body weight. The aim of the review reports physical activities that can be done by people affected by obesity in the covid-19 pandemic. The method: The scoping review method is used to map the type of physical activities for obese people. Two databases namely PubMed and EBSCO-host have been used for literature searching. The result: Ten articles were selected, namely research that included obese people of various ages such as children, adults, and the elderly. There were eight physical activities recommendations that obese people can do. There was a moderate physical activity which includes both aerobic and anaerobic training, low-intensity exercise and breathing exercise, leisure-time physical activities, home training such as pilates, yoga, and dancing, and then gym at home with simple equipment for bodyweight, isometric, resistance band, and hand-held weight exercise. Duration for exercise is recommended for 150 minutes of moderate-intensity or 75 minutes of vigorous-intensity physical activity per week. Conclusion: Many types of physical activity can be done by obese people in the covid-19 related lockdown and restriction to keep the body maintain health, to reduce body weight, and prevent exacerbations of obesity.